Pengobatan Stem Cell Embrionik: Analisis Perbandingan Hukum Positif dan Hukum Islam - Rahmadana, Nuni; Arsyad, Azman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This article aims to describe and analyze stem cell treatment findings against positive law and Islamic law. This research is a library research data collected by collecting and analyzing using content analysis (contect analysis) of literature that is representative and has relevance to the problem discussed, then reviewed, and concluded it. The data analysis used in this study is deductive and comparative research, namely by analyzing the description of general data and then drawing specific conclusions. The results of this study are materials used in the treatment of embryonic stem cells, namely Embio. In the treatment of embryonic stem cells using adult stem cells that are easily identified for the cure of conic disease. The analysis of positive law and Islamic law prohibits the use of embryonic stem cells as an observance of embryonic stem cells that cause some ethical and mathematical polymatics among the community. In this study it can be concluded that in the practice of stem cell treatment using adult stem cell types (Adult stem cells) as an effort to cure and restore health for degenarative diseases. In the analysis of positive law states that it is forbidden to use embryonic stem cells as one of the treatments as an effort to cure and recover from disease. Because the source of stem cells causes various ethical problems and dignity among the community. Meanwhile, in the analysis of Islamic law the use of embryonic stem cells exists at the dharuri level which has two legal opinions, namely the first, embryonic stem cells do not achieve the goal (Hifz an-Nafs) of maintaining the soul. Second, using embryonic stem cells as treatment is allowed if there is no treatment method.